Neuropsychological and Neuropsychiatric Endophenotypes in Amyotrophic Lateral Sclerosis - Costello, Emmet (Trinity College Dublin. School of Medicine. Discipline of Clinical Medicine, 2022)
Amyotrophic Lateral Sclerosis (ALS) is a fatal neurodegenerative disease, characterized by progressive muscle weakness and death, usually within 3-5 years from symptom onset. ALS is now recognized to be a multi-system disorder, affecting cognition and/or behaviour in up to 50% of patients. Cognitive impairment is typically screened in ALS using the Edinburgh Cognitive and Behavioural ALS screen (ECAS). In study 1 of this thesis, the equivalence of alternative ECAS versions (i.e., ECAS A-B-C) and their practice effects were assessed in healthy controls (n = 236). Alternative ECAS versions were found to be highly comparable but not statistically equivalent. Serial administration of alternative versions produced small but significant practice effects. Cognitive reserve (CR) i.e., the brains? ability to compensate for neuropathology, may moderate cognitive impairment in ALS. CR is protective against cognitive symptoms in Alzheimer?s, Huntington?s, and Parkinson?s. However, CR has yet to be examined in ALS. In study 2 of this thesis, the association between CR (measured using education, occupation and physical activity) and cognitive decline in ALS patients (n = 189) was assessed. CR was associated with better verbal fluency and language performance. CR was also associated with better baseline performance in memory, but a sharper decline over time, suggesting CR is more protective for ALS associated impairments. The most prevalent genetic cause of ALS is a mutation of the C9orf72 hexanucleotide repeat expansion, however this mutation only accounts for ~40% of Familial ALS (FALS) and ~10% of Sporadic ALS (SALS), meaning the genetic cause of most ALS cases remains unknown. Genetic studies may fail to identify risk genes because they are overly reliant on clinical description to define a phenotype. Endophenotypes (i.e., quantitative traits which lie between an illness and its underlying genetic cause) may offer a more promising approach to gene discovery as they can help identify individuals at risk prior to disease onset and provide greater statistical power in localizing and identifying disease related genes. In study 3 of this thesis, first- and second-degree relatives of ALS patients (n = 224) and healthy controls (n = 134) were recruited to examine endophenotypes in ALS. Participants were administered a neuropsychological assessment, a blood sample was taken for genetic testing, and participants were given a neuropsychiatric questionnaire to complete online. ALS relatives performed significantly worse than controls on executive functioning, language, memory and IQ domains, with large effect sizes for verbal fluency and confrontation naming tasks. Deficits were greater in relatives of FALS patients, likely due to a greater genetic burden in these individuals. ALS relatives were also characterized by initiation apathy, greater autism traits, low openness to experience and low conscientiousness traits. IQ deficits were a central component of the cognitive endophenotype in ALS relatives, but did not fully account for verbal fluency and confrontation naming deficits. Neuropsychological and neuropsychiatric outcomes clustered into two distinct sub-groups, potentially indicative of diverging risk profiles in ALS kindred. Overall, these findings suggest 3 promising candidate endophenotypes for ALS: verbal fluency, confrontation naming and openness to experience traits. Future research is needed to validate these endophenotypes on a molecular and genetic level and determine their usefulness towards gene discovery.
APPROVED
Keywords: Cognition; Endophenotype; Amyotrophic Lateral Sclerosis; Cognitive Reserve